Stirring the plot - Gerber, Daryl Wood (Gerber, Daryl Wood. Cookbook Nook mystery., 2014)
Jenna Hart has packed The Cookbook Nook chock full of everything from ghostly texts to witchy potions in anticipation of the annual fund raiser luncheon. But there's one unexpected addition to the menu: murder. When the Head Priestess of the Winsome Witches is found dead under mysterious circumstances, there's no logical answer and plenty of blame to go around. With her aunt, Vera, unable to call on her ability to foresee the future, Jenna will have to use more than just sleight of hand and a few magic tricks to conjure up the truth.